The Effect of Footrest Use on the Quality of Chest Compression during Cardiopulmonary Resuscitation (CPR) Simulation - Setiyawan Setiyawan; Desak Made Yuni Antari; Happy Indri Hapsari (Proceedings Series on Health & Medical Sciences, 2025)
Cardiopulmonary Resuscitation (CPR) is a critical life-saving procedure in the management of cardiac arrest. High-quality chest compressions significantly determine the effectiveness of CPR, including adequate depth, rate, and consistency. Rescuer stability plays a crucial role in maintaining compression quality, and the use of a footrest may help maintain ergonomic posture, reduce fatigue, and enhance the effectiveness of chest compressions. This study aims to analyse the effect of footrest use on the quality of chest compressions during CPR simulation among professional nursing students at Kusuma Husada University Surakarta. This research employed a quasi- experimental design with a post-test only control group approach. A total of 44 participants were selected using purposive sampling, with inclusion criteria of having received CPR training and possessing a normal body mass index (BMI). Observational instruments were used based on the five indicators of CPR quality according to the 2020 AHA guidelines: depth, rate, hand placement, interruptions, and chest recoil. The sample was divided into experimental and control groups. The results showed that CPR quality with the use of a footrest was predominantly in the high category (90%) compared to those without a footrest (81.8%). The Mann- Whitney test (p= .000) indicated a significant effect of footrest use on the quality of chest compressions. Further research is recommended under actual clinical conditions.